From Barriers to Assets: Rethinking factors impacting advance care planning for African Americans. Issue 3 (5th June 2018) - Sanders, Justin J.; Johnson, Kimberly S.; Cannady, Kimberly; Paladino, Joanna; Ford, Dee W.; Block, Susan D.; Sterba, Katherine R.
Abstract: Objective: We aimed to explore multiple perspectives regarding barriers to and facilitators of advance care planning (ACP) among African Americans to identify similarities or differences that might have clinical implications. Method: Qualitative study with health disparities experts ( n = 5), community members ( n = 9), and seriously ill African American patients and caregivers ( n = 11). Using template analysis, interviews were coded to identify intrapersonal, interpersonal, and systems-level themes in accordance with a social ecological framework. Result: Participants identified seven primary factors that influence ACP for African Americans: religion and spirituality; trust and mistrust; family relationships and experiences; patient-clinician relationships; prognostic communication, care preferences, and preparation and control. These influences echo those described in the existing literature; however, our data highlight consistent differences by group in the degree to which these factors positively or negatively affect ACP. Expert participants reinforced common themes from the literature, for example, that African Americans were not interested in prognostic information because of mistrust and religion. Seriously ill patients were more likely to express trust in their clinicians and to desire prognostic communication; they and community members expressed a desire to prepare for and control the end of life. Religious belief did not appear to negate these desires. Significance of results: The literature on ACP in African Americans may not accurately reflect the experience of seriously ill African Americans. What are commonly understood as barriers to ACP may in fact not be. We propose reframing stereotypical barriers to ACP, such as religion and spirituality, or family, as cultural assets that should be engaged to enhance ACP. Although further research can inform best practices for engaging African American patients in ACP, findings suggest that respectful, rapport-building communication may facilitate ACP. Clinicians are encouraged to engage in early ACP using respectful and rapport building communication practices, including open-ended questions.